Knowledge to power a nation : knowledge-based economy transformation through innovation - Abduljawad, Haytham; Overseas Development Institute (London, England) (s.l. Author, 2017)
"Knowledge to Power a Nation highlights the crucial roles of universities, industry, and government in stimulating innovation through policy-definition, business activities, and knowledge creation and exchange to drive the efforts to transform hydrocarbon-based economies into knowledge-based ones. The success of any strategy in this transformation effort is predicated on well-developed human capital. Such approaches are prone to be more effective when moderated by the development of social and professional networks and the protection of intellectual property generated from UIG collaborations. However, most importantly, the success of KBE transformation efforts begins with genuine reform of primary and secondary education systems in the GCC region (Back of the book)
1. Introduction -- 2. Knowledge management -- 3. University industry government partnerships -- 4. Innovation and the knowledge nation -- 5. Social capital: a moderating factor to innovation -- 6. Intellectual property: a moderating factor to innovation -- 7. Case study: Qatar UIG partnerships
Includes bibliographical references
Keywords: Economic development; ECONOMIC DEVELOPMENT; KNOWLEDGE; TECHNOLOGICAL INNOVATIONS